Telecentres in Mozambique: Staying On-Line - Groenendijk, Sarah; Daamen, Michael; MGBRA, Adinda Laeticia (Technical Centre for Agricultural and Rural Cooperation, 2008)
The aim of this report is to give an overview of the current phase of development of the Telecentres in Mozambique, describe their main difficulties, challenges and opportunities, proposing recommendations and a framework for action.